Efektivitas Ekstrak Daun Mangrove Avicennia Marina Pada Pertumbuhan Harian Udang Vanname ( Litopenaeus Vanname) - Linayati Linayati; Tri Yusufi Mardiana; Adinasti Antafani (Universitas Mataram, 2024)
One of the problems in shrimp farming is the high price of feed. The objective of this study was to find out the effect of the addition of mangrove extract Avecenia marina pada feed on the growth of vanname shrimp. The study used a completely randomized design (CRD) with 4 treatments and 3 replicates. The treatment used for growth is the addition of A. marina leaf extract at a dose: A (275 ppm in 500g feed), B (285 ppm in 500g feed), C (295 ppm in 500g feed), D (305 ppm in500g feed). The results of analysis of variance (ANOVA) on the growth of Vanname shrimp specific growth rate described that F value is greater than F Table, which indicates that the administration of Avicennia marina leaf extract has an effect on the best specific growth rate of 6.52% achieved in treatment D. The highest EPP calculation results amounted to 88.33% and Survival Rate reached an average of 97.25% for all treatments. Water quality during the study was within a reasonable range to support shrimp growth.